Aritifical Intelligence (AI) for EFL Writing Skills: Systematic Literature Review - Pratita Pawestri; Pratolo, Bambang Widi (Universitas Ahmad Dahlan, 2024)
This systematic literature review examines the role of Artificial Intelligence (AI) in enhancing English as a Foreign Language (EFL) writing skills. The study summarizes previous research to evaluate the effectiveness of AI-based tools such as ChatGPT, Grammarly, and Quillbot in supporting writing instruction. Several studies published between 2019 and 2024 were selected and analyzed. The findings show that AI tools can significantly help improve students’ creativity, organization, and vocabulary usage in writing. They also assist in reducing writing anxiety and increasing confidence through instant feedback and idea suggestions. However, concerns remain regarding the risks of over-reliance, loss of originality, and limited contextual understanding by AI systems. This review emphasizes the importance of using AI critically and ethically, ensuring it complements rather than replaces human input. It highlights the need for developing students' critical thinking and digital literacy alongside AI integration. The insights provided in this review can serve as a valuable reference for future empirical research and classroom practice, especially in the context of EFL writing instruction in Indonesia.